2022
DOI: 10.3399/bjgp22x719513
|View full text |Cite|
|
Sign up to set email alerts
|

Overcoming barriers to autistic health care: towards autism-friendly practices

Abstract: This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the URL above for details on accessing the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…1 These barriers and challenges are significant and have profound impact on healthcare delivery, patient and service user experience, physical and mental wellbeing, quality of life and life expectancy for autistic individuals. [2][3][4] Recent studies have shown that, because of these challenges and lack of reasonable adjustments in healthcare settings, autistic adults experienced difficulties in making healthcare appointments by telephone (62%), in feeling heard and understood (56%), difficulty in communicating with their doctor (53%) and experiencing anxiety in the waiting room environment (51%). 3 There is therefore great need for person-centred reasonable adjustments to ensure equity of healthcare provision for all service users.…”
Section: Introductionmentioning
confidence: 99%
“…1 These barriers and challenges are significant and have profound impact on healthcare delivery, patient and service user experience, physical and mental wellbeing, quality of life and life expectancy for autistic individuals. [2][3][4] Recent studies have shown that, because of these challenges and lack of reasonable adjustments in healthcare settings, autistic adults experienced difficulties in making healthcare appointments by telephone (62%), in feeling heard and understood (56%), difficulty in communicating with their doctor (53%) and experiencing anxiety in the waiting room environment (51%). 3 There is therefore great need for person-centred reasonable adjustments to ensure equity of healthcare provision for all service users.…”
Section: Introductionmentioning
confidence: 99%